Antipsychotic-induced tardive dyskinesia: update on epidemiology and management. Issue 3 (May 2019) - Widschwendter, Christian G.; Hofer, Alex
Abstract : Purpose of review: To provide an update on the frequency of antipsychotic-induced tardive dyskinesia and its management in patients with schizophrenia spectrum disorders in studies published since the last systematic review in 2008. Recent findings: Recent data about antipsychotic-induced tardive dyskinesia in patients with schizophrenia underscore the superiority of newer generation antipsychotics (21%) over first-generation antipsychotics (30%) with respect to prevalence and incidence rates. Regarding recently tested management strategies, the new vesicular monoamine transporter 2 inhibitors valbenazine and deutetrabenazine have been found to be effective and may be considered as first-line pharmacotherapy for tardive dyskinesia. Owing to quality issues of randomized controlled trials and/or small sample sizes, limited and conflicting evidence remains for most treatment strategies. Summary: The reviewed literature reveals lower prevalence rates of antipsychotic-induced tardive dyskinesia in patients treated with newer generation compared with first-generation antipsychotics. The evidence of vesicular monoamine transporter 2 inhibitors as a first-line therapy for tardive dyskinesia is well supported by several controlled clinical trials.